Separate Recognition of Building Support Components in Government Fixed Asset Accounting - Hidayat, Fajri (Pusat Publikasi Nusantara, 2023)
This study provides empirical evidence related to the application of fixed asset accounting at the level of ministries or institutions' work units, with the research location at a university in Indonesia. Through this research, it can be proven that recording the value of fixed assets in the Statement of Financial Position sourced from the conversion of the value of capital expenditures in the LRA tends to cause problems if the codification of expenditure accounts does not contain the separation of recording the components of building support. The research in this study used a descriptive method by tracing historical/documentation data. The data studied comes from the documentation of planning/budgeting, budget realization, and financial reporting in 2015, especially those related to capital expenditure and fixed asset recording. The documentation starts from DIPA, RKA-KL, SPM, Contract Documents, Supervisory Consultant Reports, Contractor Reports for Construction Development Work, Financial Reports from SAIBA applications, and data from SIMAK-BMN. Data processing was carried out using descriptive statistical methods with the help of the Microsoft Excel application program. The results of this study indicate that after separating the recognition of building support components, the value of additional fixed assets in the agency in 2015 changed significantly. This research concludes that reclassification is needed after the value of capital expenditure is converted into the value of fixed assets to comply with PSAP 07, and maintenance expenditure can be budgeted